Automated Nutrient Deficiency Detection and Recommendation Systems Using Deep Learning in Nutrition Science (International Journal of Scientific Research and Management (IJSRM), 2024)
Nutrient deficiencies affect millions globally, contributing to severe health issues and reduced quality of life. Traditional methods of diagnosing these deficiencies and recommending dietary adjustments are often time-intensive, prone to error, and lack personalization. The advent of deep learning has revolutionized nutrition science, offering automated, accurate, and scalable solutions. This paper delves into the development and application of automated nutrient deficiency detection and recommendation systems powered by deep learning. Key components of such systems include advanced data processing techniques that analyze multimodal datasets, such as biomarkers, dietary records, and food images. Convolutional Neural Networks (CNNs) excel in recognizing and quantifying nutrients from food images, while Recurrent Neural Networks (RNNs) handle time-series dietary data. Generative Adversarial Networks (GANs) and Natural Language Processing (NLP) facilitate data augmentation and textual analysis of dietary logs, respectively. These systems enable precise detection of deficiencies and generate tailored dietary plans based on individual needs, considering demographic and lifestyle factors. This article highlights case studies and practical implementations of deep learning models in real-world applications, such as AI-powered nutrition apps and biomarker-based deficiency prediction. It also addresses significant challenges, including data quality, algorithmic bias, and ethical concerns related to privacy and equity. Furthermore, the study explores future opportunities, such as integrating explainable AI, leveraging multi-modal data sources, and enhancing IoT-based tracking devices to improve recommendation systems. By bridging the gap between AI technology and nutrition science, these systems hold the potential to revolutionize global dietary health, offering scalable, personalized, and efficient solutions to combat nutrient deficiencies.